The global multidimensional poverty index: harmonised level estimates and their changes over time - Suppa, N; Kanagaratnam, U (Oxford Poverty and Human Development Initiative, 2023)
This paper describes the database The Global Multidimensional Poverty Index (MPI): Harmonised Level Estimates and their Changes over Time. The global MPI is an international poverty measure based on ten deprivation indicators in three dimensions: health, education, and living standards. The database contains estimates for the multidimensional poverty index itself (the adjusted headcount ratio), related partial indices such as the headcount ratio, the intensity, indicator-specific indices, and several auxiliary statistics as well as changes over time for most quantities. For this database all deprivation indicators have been harmonised over time. Our database covers estimates for 84 countries and 814 subnational regions for up to four points of observation. The estimates are based on 211 individual survey datasets, mostly the Demographic Health Survey (DHS) and the Multiple Indicator Cluster Survey (MICS). Combining information of different dimensions of human well-being, the global MPI inherently invites interdisciplinary research.